(untitled) (World Bulletin of Management and Law, 2022)
Taking into account that the procedures and practices used in today’s practice regarding the loan agreement, business practices formed in the industry, and the legislation aimed at regulating lending activities in the banking and financial sector are not provided for in the FC and have formed norms that meet the modern requirements of today’s financial market, the loan agreement has the following legal symbols showing: one-way or two-way, real and consensual contract, free or paid contract. This characterization of the loan agreement results from the terms of the agreement and the requirements for lending and receiving loans established in the mutual agreement of the parties. In particular, if in the loan agreement the parties specify the lender’s obligation to pay the loan amount in the future, if they agree to repay the loan amount with interest, then the loan agreement with this content is included in the consensual, bilateral (mutual) and fee-based contracts. If a loan agreement is executed between citizens and the loan amount is to be returned without interest, such a loan agreement is considered a real, one-sided and gratuitous agreement.